PERAN SISTEM MANAJEMEN INFORMASI DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PENDIDIKAN ISLAM DI ERA DIGITAL - Muhammad Rizky Mubarok; Safaat Safaat (STKIP Pesisir Selatan, 2025)
The rapid development of information and communication technology in the digital era has significantly transformed the management of Islamic educational institutions. This study aims to analyze the role of the Information Management System (IMS) in enhancing the effectiveness of Islamic education management amid the dynamics of digital transformation. Using a descriptive qualitative approach through literature review, this research examines academic references and previous studies related to the implementation of IMS in Islamic educational contexts. The findings reveal that IMS plays a strategic role in improving administrative efficiency, financial transparency, and institutional governance effectiveness. The core components of IMS include student data management, curriculum and learning management, financial administration, human resource management, and evaluation and reporting systems. However, its implementation still encounters several challenges, such as limited infrastructure, digital literacy gaps, and organizational resistance to change. Overall, the adoption of IMS contributes to the realization of modern, accountable, and spiritually grounded Islamic education governance.